Simultaneous Characterization of Deletional and Nondeletional Globin Gene Mutations by Multiplex Real-Time-Polymerase Chain Reaction and High-Resolution Melting Curve Analysis. (2nd September 2020) - Nuinoon, Manit; Horpet, Dararat
Abstract: Both deletional and nondeletional globin gene mutations are common in Southeast Asians. Normally, deletional gene mutations are characterized separately from nondeletional gene mutations. Therefore, we developed a new approach of multiplex real-time polymerase chain reaction (qPCR) followed by high-resolution melting (HRM) analysis without a fluorescently-labeled probe for the simultaneous detection of deletional and nondeletional gene mutations in a single tube. Three sets of primer pairs were used to establish the qPCR-HRM method that was used to genotype more than 20 different globin genotypes. Twenty known genotypes were used to optimize the qPCR and HRM conditions. Eight genotypes were used to determine the reproducibility of the method. A total of 351 blinded known DNA samples were used for the validation study in three separate reactions and revealed 16 distinct patterns of fragments and/or HRM. The melting temperatures (Tm) of the 3.5 kb, – – THAI, HBB -FR2 (exon 1 of the HBB gene), – – SEA (Southeast Asian), α2 and 3'-ψζ1 fragments were 79.44, 81.01, 86.47, 87.89, 90.54 and 94.15 °C, respectively. The HRM analysis was performed with the HBB -FR2 fragment to differentiate several alleles. We report a rapid and high-throughput technique that showed 100.0% concordance and low variability for each run. Our developed technique is one of the alternative techniques recommended for screening samples with both deletional and nondeletional globin gene mutations.